2019
DOI: 10.1183/23120541.00123-2019
|View full text |Cite
|
Sign up to set email alerts
|

Suppression ofFENOwith observed inhaled corticosteroid therapy in severe asthma: is it a useful test in clinical practice?

Abstract: Biologic therapies are used in atopic and/or eosinophilic asthma that remains uncontrolled on optimised conventional therapy [1–4]. Nonadherence with prescribed therapy is common in severe asthma [5] and National Health Service England's commissioning guideline [6] advises adherence assessment prior to commencing biologic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Therefore in all but one patient in this group who did not progress to biologic therapy, their underlying asthma did not dictate an ongoing need for maintenance prednisolone; additionally the one remaining patient would have proceeded to biologic therapy with their consent. These data builds on the report of F aruqi et al [ 11 ] who described 6-month outcome in 46 patients who fulfilled UK prescribing criteria for biologic therapy; following FeNOSuppT, 19 of 46 (40%) were identified as non-adherent and 14 did not progress to biologic therapy during the 6-month follow-up. Notably, in this cohort, none were on maintenance oral corticosteroid at initial assessment, whereas in our cohort over 50% were prescribed maintenance prednisolone, which is typical of patients referred to specialist care in the UK [ 21 ].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Therefore in all but one patient in this group who did not progress to biologic therapy, their underlying asthma did not dictate an ongoing need for maintenance prednisolone; additionally the one remaining patient would have proceeded to biologic therapy with their consent. These data builds on the report of F aruqi et al [ 11 ] who described 6-month outcome in 46 patients who fulfilled UK prescribing criteria for biologic therapy; following FeNOSuppT, 19 of 46 (40%) were identified as non-adherent and 14 did not progress to biologic therapy during the 6-month follow-up. Notably, in this cohort, none were on maintenance oral corticosteroid at initial assessment, whereas in our cohort over 50% were prescribed maintenance prednisolone, which is typical of patients referred to specialist care in the UK [ 21 ].…”
Section: Discussionsupporting
confidence: 66%
“…The FeNO suppression test (FeNOSuppT) can identify poor background adherence to ICS in patients with "difficult to control" asthma [8] and we have previously demonstrated its' utility as a 'home-based' test using smart inhaler technology in predicting biomarker profile and suitability for biologic therapy when patients are adherent with high dose ICS/LABA treatment [9]. The availability of biologic agents targeting specific cytokines in the inflammatory cascade has led to improved control and reduced corticosteroid exposure in patients with T2-high asthma [10] and small single centre cohort studies have suggested that a positive FeNOSuppT is associated with lower transition to biologic therapy [11,12] Biologics are costly and potentially life-long, therefore it is important to manage other conditions impacting upon asthma control and ensure patients are adherent to inhaled corticosteroids (ICS) prior to committing to biologic agents. The purpose of this study was to examine longer term outcomes following FeNOSuppT in a multicenter setting and determine whether subjects with a positive test experienced an improvement in exacerbation frequency and were less likely to proceed to biologic treatment; in essence, could a seven day assessment of adherence help predict future outcome in terms of progression to biologic therapy?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has obvious clinical utility as it can quickly identify those patients who are unlikely to achieve control of type-2 inflammation using inhaled treatment alone and could progress quickly to biologic therapy, but in parallel it can identify those patients where the clinical focus needs to be on better adherence with inhaled treatment. A recent systematic literature review [ 66 ] examining the assessment of adherence to corticosteroids in asthma by drug monitoring or F ENO supports this use of F ENO SuppT as well as outcome data from small single centre studies [ 67 , 68 ]. Additionally, this was further supported by the largest case series from the RASP-UK programme which demonstrated that a positive F ENO SuppT was associated with significantly fewer patients progressing to biologic therapy and a significantly greater chance of being discharged from hospital [ 69 ].…”
Section: Measuring and Identifying Non-adherencementioning
confidence: 97%
“…The observation that FeNO predicts inhaled corticosteroid (ICS)-responsiveness has led to the development of the FeNO suppression test to identify non-adherence in difficult-to-treat, FeNO-high asthma 4 5. One-third of patients have a persistently raised FeNO and disease burden despite objectively measured adherence to high-dose ICS 4 6–8. This group of ‘FeNO non-suppressors’ have been presumed ‘corticosteroid resistant’,9 but the longitudinal investigation of inflammatory changes over the course of a FeNO suppression test has not been reported.…”
Section: Introductionmentioning
confidence: 99%